Cancer Nanotechnology Methods and Protocols - Grobmyer, Stephen R.; Moudgil, Brij M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
Early detection of cancer at the cellular level, even before anatomic anomalies are visible, is critical to more efficacious and cost effective diagnosis and therapeutic advances. In Cancer Nanotechnology: Methods and Protocols, an international panel of experts provide the most recent, cutting-edge, "how-to" approaches developed and employed by researchers in a variety of disciplines to identify cancer specific biomarkers, construct suitable multifunctional targeted nanostructure platforms, along with enhanced imaging and therapeutic applications. Covering such topics as multifunctional and multimodal nanoparticles, nanoparticle mediated cancer theranostics, molecular targets for cancer nanotechnology, and nanoparticles for non-invasive image-guided cancer therapy, the volume addresses the key challenges of the field today, specifically targeted and localized delivery of the drugs. As a volume in the highly successful Methods in Molecular Biology™ series, the protocols chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Cancer Nanotechnology: Methods and Protocols integrates cancer biology, clinical oncology, molecular cancer imaging, materials science and chemical engineering, biomedical engineering, toxicology, computer science, electrical engineering, chemistry, physics, and mathematics in order to achieve the vital goals of nanotechnology-mediated early cancer detection and more efficacious and less toxic therapies for these devastating diseases.
What Is Cancer Nanotechnology? -- Molecular-Targeted Therapy for Cancer and Nanotechnology -- Enhanced Permeability and Retention (EPR) Effect for Anticancer Nanomedicine Drug Targeting -- Nanoparticle Characterization for Cancer Nanotechnology and Other Biological Applications -- Multimodal Nanoparticulate Bioimaging Contrast Agents -- Gold Nanocages for Cancer Imaging and Therapy -- Nanoshells for Photothermal Cancer Therapy -- Gold Nanorods: Multifunctional Agents for Cancer Imaging and Therapy -- Polymeric Micelles: Polyethylene Glycol-Phosphatidylethanolamine (PEG-PE)-Based Micelles as an Example -- Fluorescent Silica Nanoparticles for Cancer Imaging -- Polymeric Nanoparticles for Drug Delivery -- Synthesis, Characterization, and Functionalization of Gold Nanoparticles for Cancer Imaging -- Identification of Pancreatic Cancer-Specific Cell-Surface Markers for Development of Targeting Ligands -- Preparation and Characterization of Doxorubicin Liposomes -- PEGylated Nanocarriers for Systemic Delivery -- Nanoparticle–Aptamer Conjugates for Cancer Cell Targeting and Detection -- Targeting of Nanoparticles: Folate Receptor -- Magnetic Aerosol Targeting of Nanoparticles to Cancer: Nanomagnetosols -- LHRH-Targeted Nanoparticles for Cancer Therapeutics -- Antibody Targeting of Nanoparticles to Tumor-Specific Receptors: Immunoliposomes -- Photoacoustic Tomography for Imaging Nanoparticles -- Current Applications of Nanotechnology for Magnetic Resonance Imaging of Apoptosis -- Applications of Gold Nanorods for Cancer Imaging and Photothermal Therapy -- Use of Nanoparticles for Targeted, Noninvasive Thermal Destruction of Malignant Cells -- Colloidal Gold: A Novel Nanoparticle for Targeted Cancer Therapeutics -- Liposomal Doxorubicin and nab-Paclitaxel: Nanoparticle Cancer Chemotherapy in Current Clinical Use.
Keywords: Oncology .; Cancer research; Laboratory medicine; Oncology; Cancer Research; Laboratory Medicine